Social Conservation on the Women Habitus in Eastern Coast of Pati Regency - Lestari, Puji (Faculty of Social Science, Universitas Negeri Semarang, 2020)
This research was conducted with the aim to; 1) explore social conservation on the women habitus in eastern coast (Eastern Coastal Pantura) of Pati Regency; 2) identify the development of social conservation on the women habitus in eastern coast of Pati Regency. In addition, this study also provides knowledge and awareness to eastern coastal women in Pati Regency on the importance of social conservation efforts in the community. This qualitative research was carried out with a descriptive analytical approach. Data collection techniques used interview, observation and documentation techniques. The acquired data will be processed and analyzed with triangulation techniques to obtain valid data. The results indicate the data that women have a strategic position in social conservation in the eastern coastal communities of Pati Regency. Women are adaptive to social changes taking place around them, developing social conservation in their habitus in the family. Women in the family, through their parenting; transfer of values, typical traditions of coastal communities undergoing social change; maintaining harmony in the family in a dynamic society; follow, prepare and implement traditions, cultures that are routinely carried out in a society filled with symbols of tradition and beliefs. All of these that women are doing, without them knowing that they all have an influence on the sustainability of cultural traditions and beliefs in society, and continue to persist. Women are able to play a role in their field, accepting new doxas arising from the interaction of habitus and their field. Its development can be conducted in a structured way from the village level to the Dasawisma group through training and character education simulations, tracking traditions and local wisdom, and developing social intelligence for women. In this activity, the involvement of community as well as religious leaders and women in designing activities is very necessary.